.NET framework essentials - Thai, Thuan L. (O'Reilly, 2001)
.NET Framework Essentials is an objective, concise, and technical overview of the new Microsoft .NET Framework for developing web applications and services. Specifically written for intermediate to advanced VB, C/C++, Java, and Delphi developers, .NET Framework Essentials is also useful to system architects and leaders who are assessing tools for future projects. The authors devote special attention to the writing of .NET components plus web applications and services. This book takes on all of the most important .NET Framework topics--from the underlying Common Language Runtime (CLR) to its specialized packages for ASP.NET, Web Forms, Windows Forms, XML and data access (ADO.NET). The authors survey each of the major .NET languages, including VB.NET, C#, and Managed C++, as well as MSIL, the intermediate language understood by the CLR. They've included working code samples in every .NET language. Compact and free of fluff or proprietary hype, .NET Framework Essentials is an outstanding value for experienced programmers and architects who need to get up to speed quickly on a far-reaching new technology.